PENGARUH STRATEGI PEMBELAJARAN BERBASIS PROYEK DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI SMA NEGERI 1 SIPIROK DAN SMA NEGERI 1 ARSE KABUPATEN TAPANULI SELATAN - Gulmat Siregar; Sri Ulfa Sentosa (Jurnal Kajian Pendidikan Ekonomi, 2015)
Purpose of his research for reveal: (1) result of economic studies with high motivation  project based learning higer than lecture method varies, (2) result of economic studies with high motivation of student use project based learning higer than result of economic studies with high motivation of student use lecture method varies (3) result of economic studies with lower motivation of student use project based learning higer than result of economic studies with lower motivation of student use lecture method varies (4) presence interaction project based learning between motivation, presence interaction lecture method varies between motivation to learn. Type of reaches is Quasi Experiment used  factorial  2x2 design. Population in this research is all class XI IPS in SMA Negeri I Sipirok and SMA Negeri 1 Arse South of Tapanuli distict. Samples taken with using purposive sampling techniques, selected students in the class XI.IPS1 SMAN 1 Sipirok (experimental class) and class XI.IPS1 SMA Negeri 1 Arse (control class). Gather data filter through the test results and the most adapted'll analyzed with t-test and ANOVA. Therefore, there is a conclusion that make project based learning method could increase the result of student study and motivationKeyword : Project Based Learning, , Motivation of student, Result of economic studies